Sustainable strategy for the waste management in Turkmenistan - Anna Korostova (Helmholtz-Zentrum für Umweltforschung (UFZ), 2020)
This study will concentrate on the case of Turkmenistan, newly industrialized country appeared in the world map after the collapse of Soviet Union in early 90ties. Along with other countries they were engaged with the rebuilding of their new economy and the issues of waste management were set apart. In the recent years, the need to adhere to international norms in order to achieve sustainable economic development requires to consider environmental impact of the activities, including in the waste management. Recycling and waste management gained more attention in the country, but there is still a lot of work to do. The aim of this work is to provide a comprehensive overview of waste management in Turkmenistan and to provide recommendations and solutions in order to achieve sustainable development goals, adjusting the existing tools and practices to the case of this country. An increase of share of the circular economy as well as the reduction of disposed waste quantities are considered as the main goal of proposed activities.
Keywords: 330; Abfallwirtschaft; Kreislaufwirtschaft; Turkmenistan